Imaging of Martian Circulation Patterns and Atmospheric Tides Through MAVEN/IUVS Nightglow Observations. Issue 8 (5th August 2020) - Schneider, N. M.; Milby, Z.; Jain, S. K.; González‐Galindo, F.; Royer, E.; Gérard, J.‐C.; Stiepen, A.; Deighan, J.; Stewart, A. I. F.; Forget, F.; Lefèvre, F.; Bougher, S. W.
Abstract: We report results from a study of two consecutive Martian years of imaging observations of nitric oxide ultraviolet nightglow by the Imaging Ultraviolet Spectrograph (IUVS) on the Mars Atmosphere and Volatile Evolution (MAVEN) mission spacecraft. The emission arises from recombination of N and O atoms in Mars' nightside mesosphere. The brightness traces the reaction rate as opposed to the abundance of constituents, revealing where circulation patterns concentrate N and O and enhance recombination. Emissions are brightest around the winter poles, with equatorial regions brightening around the equinoxes. These changes offer clear evidence of circulation patterns transitioning from a single cross‐equatorial cell operating during solstice periods to more symmetric equator‐to‐poles circulation around the equinoxes. Prominent atmospheric tides intensify the emissions at different longitudes, latitude ranges, and seasons. We find a strong eastward‐propagating diurnal tide (DE2) near the equator during the equinoxes, with a remarkably bright spot narrowly confined near (0°, 0°). Wave features at the opposite winter poles are dissimilar, reflecting different circulation patterns at perihelion versus aphelion. LMD‐MGCM simulations agree with the patterns of most observed phenomena, confirming that the model captures the dominant physical processes. At the south winter pole, however, the model fails to match a strong wave‐1 spiral feature. Observed brightnesses exceed model predictions by a factor of 1.9 globally, probably due to an underestimation of the dayside production of N and O atoms. Further study of discrepancies between the model and observations offers opportunities to improve our understanding of chemical and transport processes controlling the emission. Plain Language Summary: The MAVEN spacecraft orbiting Mars has obtained a new type of imaging data which reveals the effects of global‐scale winds and waves in the upper atmosphere. Ultraviolet emissions confirm the expected change of wind patterns with season and pinpoint an unusually bright spot on Mars' nightside. Computer model runs successfully match many of the observed features and allow an examination of the underlying physical causes. Differences between the model and observations offer insights on how to improve the model. Key Points: The MAVEN spacecraft orbiting Mars has obtained a new type of nightside imaging data which reveals the effects of global‐scale winds and waves in the upper atmosphere Ultraviolet nightglow emissions confirm the expected change of circulation patterns with season and pinpoint an unusually bright spot on Mars' nightside A Mars general circulation model successfully matches many of the observed features and allows an examination of the underlying physical causes